Assessment of 2DH and pseudo-3D modelling platforms in a large saline aquatic system: Lake Urmia, Iran - Zeinoddini, M.; Tofighi, M. A.; Bakhtiari, A. (Hydrological processes, 2014)
The main objective of this paper is to provide comparative quantitative examinations on the capabilities of two‐dimensional horizontal and pseudo‐three‐dimensional (3D) modelling approaches for simulating spatial and temporal variability of the flow and salinity in Lake Urmia, Iran. The water quality in the lake has been an environmentally important subject partly because this shallow hypersaline aquatic ecosystem is considered to be one of the largest natural habitats of a unique multicellular organism, Artemia urmiana. This brine shrimp is the major food source for many of the protected and rare shorebirds that visit the lake. A. urmiana can grow and survive in certain ranges of salinity, and their disappearance could lead to an alteration of existing equilibria. The lake has also experienced considerable man‐made changes during the past three decades. A newly built crossing embankment almost divided the lake into two northern and southern halves. A relatively small opening of 1.25 km in the new embankment provides water connections between the two halves. As a result, the flow and salinity regimes have been significantly changed. This might have had adverse serious impacts on the lake ecosystem. In the current study, the two‐dimensional horizontal hydrodynamic model has been found to provide reasonable predictions for the flow regime in the lake, whereas its salinity predictions have not been consistent with the field observations. The pseudo‐3D model has produced results fairly close to the salinity measurements and its temporal and spatial variations. The pseudo‐3D model has been used for evaluating the embankment effects on the lake hydrodynamics and on the salinity conditions. The effectiveness of introducing a different number or length of openings in the embankment for restoring the pre‐embankment conditions has also been examined. These remedy options have been found not to offer substantial improvements to the lake's existing ecosystem. Copyright © 2013 John Wiley & Sons, Ltd.